Analisis Teorema Bayes Dalam Mendiagnosa Penyakit Tanaman Pisang - Zunaidi, Muhammad; Pane, Usti Fatimah Sari Sitorus; Nasyuha, Asyahri Hadi (STMIK Budi Darma, 2021)
Most of Indonesia's population earns a living as farmers who mostly cultivate various types of plants, one of which is the banana plant. Banana plant (Musa Paradisiaca L) is one of the horticultural crops that can be planted intensively due to very supportive soil and climatic conditions, especially in North Sumatra. However, the productive growth of banana plants in Indonesia is getting lower, this is due to the lack of knowledge of farmers about banana plant diseases and how to overcome them, another reason is the lack of agricultural managers who provide counseling to farmers about types of banana plant diseases and their prevention and prevention. In this study, we will take advantage of the development of analysis that adopts the process and way of thinking of humans, namely Artificial Intelligence or artificial intelligence which is often called the Expert System with the Bayes Theorem algorithm that relies on probability values, so that it can provide diagnostic results that are in accordance with symptoms based on the knowledge base obtained from expertise. an expert in the field of banana plant diseases. The research will provide solutions for handling or preventing disease based on the rules that have been obtained from the expertise of an expert in the field of banana plants. So the analysis of the Bayes theorem algorithm is feasible to implement and can help banana farming communities in preventing disease and can help increase the productivity of banana plants